2m+1=27

Simple and best practice solution for 2m+1=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+1=27 equation:


Simplifying
2m + 1 = 27

Reorder the terms:
1 + 2m = 27

Solving
1 + 2m = 27

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 2m = 27 + -1

Combine like terms: 1 + -1 = 0
0 + 2m = 27 + -1
2m = 27 + -1

Combine like terms: 27 + -1 = 26
2m = 26

Divide each side by '2'.
m = 13

Simplifying
m = 13

See similar equations:

| 6x+x-8=6x+7 | | 11k-11=7k-(-21) | | (8x^2+2x-6)-(5x^2-3x+2)=0 | | 2g-4=-8 | | 2(x-1)-3x=7 | | 15/x+5*3=40+6x | | 4a^2-16a^2=0 | | 3x+5=-1x-7 | | y^2-2y+1=64 | | Y=Go+d | | 800+160-30=0 | | 2(x+20)=2(x-10) | | 5/6x=-218 | | 7/5x=3/10 | | (x)(x-2)=35 | | Sin^2(X)=2cosx | | 800(100+30)=0 | | 102=(x+18)+(x-12)+x | | -x+13=x+6 | | 21d=-63 | | 56x=-218 | | M=57 | | -5y+10x=-15 | | 168=-6(8x-4) | | 4p(p+2)=0 | | 665/7 | | 4(n-3)=28 | | -3(-3+5x)=-6 | | -7(2x-6)=154 | | -9x+5x=16 | | 6(-3+2b)=-90 | | V=pir^2h2/3 |

Equations solver categories